(untitled) - Bauer, Larry A. (New York, 2006)
Designed for pharmacists and clinicians responsible for adjusting drug dosages based on the patient blood serum concentrations and other parameters, this indispensable, portable reference offers a variety of ways to perform pharmacokinetic calculations. Features calculation methods, algorithms for choosing the best calculation method, and case studies.
Keywords: Pharmacokinetics,Dược động học